Програмна система для організації та контролю проведення заходів. Підсистема організатора заходів - Жорняк, М. О. (ХНУРЕ, 2023)
Nowadays, the world needs automation of all possible processes to make our lives easier and more convenient. The field of organizing mass events is no exception, indeed it requires a convenient tool to improve ticket sales or increase attendance and effectiveness rate for various educational events. That is the reason why it is suggested to consider creating a versatile service, that provides automated tools for organising and monitoring events: from outdoor recreation to evacuating people from hotspots. The service will be designed for a regular user, an event organizer and a controller, but we will consider part of the functionality for the organizer.